ASSESSMENT AND EVALUATION OF POWTOON MEDIA BASED ON ANALYSIS, DESIGN, DEVELOPMENT, IMPLEMENTATION, EVALUATION (ADDIE) - Ilham Ismail Lubis; Durrah Sakinah; Kurnia Purnama Sari (Universitas Negeri Makassar, 2024)
The aim of this research is that ADDIE-based Powtoon media can improve students' abilities in thinking creatively and developing arguments. This research uses the Research and Development research method. Involving experts (6 teachers) to assess and validate the media using media validation instruments (construct, language and technology). Meanwhile, to assess the practicality of media using instruments to see the influence of the media involving 30 students and 15 KKG teachers. Data were analyzed using SPSS V22 descriptively to describe the results of the media assessment. Based on the research results, the average validation results carried out on 30 students and 15 KKG teachers regarding Powtoon-based learning media were 3.51 percent and 3.95 percent, namely in the Quite Influential category, respectively. Furthermore, the results of the Practicality Analysis carried out on 5 teachers regarding Powtoon-based learning media were 4.06 percent in the Influential category. In this case the media used is valid and has an influence on the teaching and learning process.